2008
DOI: 10.1159/000130425
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol plus Betamethasone Dipropionate Scalp Formulation Is Effective and Well Tolerated in the Treatment of Scalp Psoriasis: A Phase II Study

Abstract: Background: There is a need for more effective therapy for scalp psoriasis. Objective: To assess the efficacy and safety of a 2-compound scalp formulation including calcipotriol and betamethasone dipropionate in the treatment of scalp psoriasis. Methods: Patients (n = 218) with scalp psoriasis were randomized to treatment with the 2-compound scalp formulation (n = 108) or betamethasone dipropionate in the same vehicle (n = 110). The treatments were applied once daily on the scalp for up to 8 weeks. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…37 A regimen using a combination of a corticosteroid and a vitamin D analogue for scalp psoriasis can help to minimize irritation and the amount of topical corticosteroids used. [26][27][28][29]53 In one small study, the ointment combination of calcipotriene 50 g/g and betamethasone dipropionate 0.5 mg/g was effective in treating resistant scalp psoriasis. 27 Head-to-head studies comparing the combination of topical corticosteroids and vitamin D analogues to each therapy alone in scalp psoriasis will be required to properly evaluate efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…37 A regimen using a combination of a corticosteroid and a vitamin D analogue for scalp psoriasis can help to minimize irritation and the amount of topical corticosteroids used. [26][27][28][29]53 In one small study, the ointment combination of calcipotriene 50 g/g and betamethasone dipropionate 0.5 mg/g was effective in treating resistant scalp psoriasis. 27 Head-to-head studies comparing the combination of topical corticosteroids and vitamin D analogues to each therapy alone in scalp psoriasis will be required to properly evaluate efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results from a previous clinical trial, 20 it was assumed that the comparisons of the two-compound scalp formulation versus betamethasone dipropionate alone would have 90% power and versus calcipotriene or vehicle alone would have more than 99.5% power, with 540 patients in the twocompound scalp formulation group, 540 patients in the betamethasone dipropionate group, 270 patients in the calcipotriene group, and 135 patients in the vehicle group. Thus approximately 90% power would be achieved to reject the combined null hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This is a lipophilic gel formulation, particularly suitable for application to the scalp that combines the keratinocytes differentiation action of the vitamin D 3 analogues with the anti-inflammatory effect of steroids reducing the side-effect profile of the single topical agent. Previous studies showed the efficacy and safety of this combination in mild-to-moderate plaque-type psoriasis of body and scalp (7)(8)(9)(10)(11)(12)(13)(14). However, maintenance strategies after complete remission have been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%